BAHASA, SASTRA, ZAMAN EDAN, DAN INDUSTRI KREATIF - Ayu Sutarto (LITERASI: Indonesian Journal of Humanities, 2014)
The ability of using particular language is closely related to social promotion. However, not all languages that have large speakers get the chance. Java language - whose speakers are ranked the 11th of the 6,000 languages in the world - has not been used to support social promotion. In Java, there are literary expressions whose meanings penetrate cultural, social, political, economic, and security events or phenomena, namely ‘crazy era’. The phrase is to criticize the socio-political life which ignores the Javanese cultural values and norms. Change is a necessity. However, it does not mean to tear down the noble values of a community or nation, because the socio-cultural life will collapse, the pride and dignity of a nation will be blurred or lost because the people are uprooted from their cultural roots. Language and literature are a valuable cultural heritage. Language is a buffer of identity and literary reflection of the inner world of its owner. In this era of creative industry, literature and language that have such great speakers and heirs as the Javanese language, can become an instrument to strengthen the social, moral, and cultural promotions. Ronggowarsito’s Kalatida can be utilized for the sake of it. Keywords: language, creative industries, literature, crazy times, promotion